Causes of Girls Drop Out from Primary Schools in Tehsil Bahrain District Swat, KPK Pakistan - Bibi, Aqsa; Ahmad, Waqar (Asian Journal of Contemporary Education, 2019)
Getting education is very important for both boys and girls. However, there are female children who do not complete school cycle and leave school before its completion which is one of the concerning issues for the Ministry of Education in Pakistan. To know why these girls drop out of school, the study provides some brief information on it. To get information on the above issue, structured interviews were used. The study was conducted in 4 Girls primary schools of Tehsil Bahrain district SWAT. Data was collected from sample of 80 respondents, in which (11 dropout girls from Govt Girls Primary School Madyan Swat, 16 from Govt Girls Primary School Ayeen Swat, 22 dropout girls from Girls Primary School Darolai Swat, 3 dropout girls from Girls Primary School Jail Bahrain Swat.20 mothers of the dropout students and 8 teachers. After collecting information, some of the main causes for the dropout were found as work to earn some money for support of family (poverty), moving from one place to another, culture of the village, punishment, teachers’ behavior, long distance from house to school and lack of text books and facilities. By looking to the findings of the study, there is a need of other researches in the area.